2017
DOI: 10.1016/j.nlm.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal-perirhinal cortical communication is necessary for flexible response selection

Abstract: The ability to use information from the physical world to update behavioral strategies is critical for survival across species. The prefrontal cortex (PFC) supports behavioral flexibility; however, exactly how this brain structure interacts with sensory association cortical areas to facilitate the adaptation of response selection remains unknown. Given the role of the perirhinal cortex (PER) in higher-order perception and associative memory, the current study evaluated whether PFC-PER circuits are critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 108 publications
7
65
2
Order By: Relevance
“…In tasks that require choice between two potential outcomes presented simultaneously, rats tend to initially default to an egocentric response‐based strategy before learning to apply a more flexible task‐specific strategy (Hernandez et al, ; Lee & Solivan, ; Lee & Byeon, ; Jo & Lee, ). For example, both young and aged rats develop a strong bias toward selecting an object on a specific side of a choice platform (i.e., left vs. right) before learning to recognize and compare visual features and select a target object over a lure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In tasks that require choice between two potential outcomes presented simultaneously, rats tend to initially default to an egocentric response‐based strategy before learning to apply a more flexible task‐specific strategy (Hernandez et al, ; Lee & Solivan, ; Lee & Byeon, ; Jo & Lee, ). For example, both young and aged rats develop a strong bias toward selecting an object on a specific side of a choice platform (i.e., left vs. right) before learning to recognize and compare visual features and select a target object over a lure.…”
Section: Resultsmentioning
confidence: 99%
“…For example, both young and aged rats develop a strong bias toward selecting an object on a specific side of a choice platform (i.e., left vs. right) before learning to recognize and compare visual features and select a target object over a lure. Suppression of side bias as training progresses has been shown to correspond with an increase in correct responses guided by the task‐specific rule (Hernandez et al, ; Lee & Byeon, ). Based on the fact that both young and aged rats showed more checking behavior and better performance on Lure 1 trials, but less checking and poorer performance on Lure 2 and Lure 3 trials (Figures B and B), we asked whether rats showed evidence of suppressing a side bias when making correct responses across these trial types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were trained on the biconditional association task (BAT) as previously published (8,10,12). Briefly, rats were first trained to alternate between left and right arms of a V-shaped maze (see Figure 1) with a macadamia nut reward at the end of each arm.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…While the objects remain the same throughout testing, the correct choice varies as a function of location within the maze. As this task requires the integration of object information with spatial location to flexibly update behavior, it depends on connectivity between the prefrontal cortex, perirhinal cortex and hippocampus [21][22][23]. Female rats have been documented as performing differently from males on other prefrontal cortical dependent behaviors, such as deliberative decision making in the face of risk of punishment [24].…”
Section: Introductionmentioning
confidence: 99%